Teachers’ Gestures in EFL Classroom - Afdaliah, Nihla (LP2M IAIN Sultan Amai Gorontalo, 2022)
The research analyzed the teachers’ gestures in EFL classrooms. It covered the teachers’ gestures, the functions of the teachers’ gestures, and the effect of the teachers’ gestures on the students. The research applied a qualitative research design. The subjects of the research were 2 English teachers and 14 students of a senior high school in Majene. The research instruments were classroom observation, teachers’ and students interviews. The results of this research revealed that the teachers performed hand gestures and head gestures in the classroom. The hand gestures were pointing, beckoning/inviting, giving examples, clapping hands, knocking on the table, hitting the whiteboard, illustrating, and numbering. In contrast, for head gestures, they used nodding and shaking head. The teachers used the gestures mainly regarding management, regulation, input, and instruction. But in some meetings, one of the teachers used head gestures combined with a smile when rewarding students and showing affection. These teachers’ gestures were primarily used in conjunction with words or verbal messages (speech-related gestures) to complement, accentuate, and repeat the words. On the other hand, a small number of gestures are also used to substitute words. These gestures are stand-alone or are called speech-independent gestures. Teachers' use of gestures in the classroom consciously and unconsciously affects students and the learning process. Students agreed that using gestures by the teacher could improve their understanding of the material. However, using improper or too many gestures can distract their focus, making it difficult for them, to be nervous and difficult to engage in the learning process. So, it is urgent for the teachers to understand that some gestures should be increased or decreased to create a better learning atmosphere.